2019
DOI: 10.1002/ep.13258
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the adsorption of H2S by ZnO–TiO2 and Ni–ZnO–TiO2 nanoparticles: An adsorption isotherm and thermodynamic study

Abstract: Nanoparticles were synthesized by the sol–gel method and evaluated for adsorption of hydrogen sulfide using a continuous fixed‐bed column. The effects of the parameters were examined, and the optimum values for nanoparticles were found to be mass of adsorbent 0.2 g, gas volume 5.7 L, flow rate 0.22 L min−1, and gas pressure 7 Psi at 12 °C. These conditions resulted in a maximum adsorption of H2S of 83.24% and 90.43% for ZnO–TiO2 and Ni–ZnO–TiO2 nanoparticles, respectively. The equilibrium data were best repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…During the adsorption process, the biogas is contacted with an adsorbent in which the H 2 S is collected on the surface and interior microstructure of the adsorbent. Several types of adsorbents have been proposed in the literature, including metal oxides, silica gel, zeolites, synthetic resins, and activated carbon [8,[15][16][17][18][19][20][21]. Activated carbon has been widely used for the treatment of wastewater and waste gases.…”
Section: Introductionmentioning
confidence: 99%
“…During the adsorption process, the biogas is contacted with an adsorbent in which the H 2 S is collected on the surface and interior microstructure of the adsorbent. Several types of adsorbents have been proposed in the literature, including metal oxides, silica gel, zeolites, synthetic resins, and activated carbon [8,[15][16][17][18][19][20][21]. Activated carbon has been widely used for the treatment of wastewater and waste gases.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the broad absorption band at 3426 cm −1 can be attributed to the stretching vibration of -OH and -NH.while 2950 cm −1 , 2830 cm −1 , and 2715 cm −1 are attributed to the stretching vibration of C-H, 1361 cm −1 is the peak of the bending vibration of C-H, respectively (Zheng et al, 2017;Ren et al, 2021); At 1590 cm −1 , a clear amide II band appears, which belongs to the bending vibration of N-H, and 1157 cm −1 is the peak of the bending vibration of C-H. The amide II band at 1590 cm -1 belongs to the bending vibration of N-H, and the peaks at 1157 cm −1 and 1062 cm −1 belong to the absorption of the C-N stretching vibration (Mohammadi et al, 2019). Compared with the native chitosan, the intensity of the absorption band at 3426 cm −1 decreased, indicating that the hydroxyl group of chitosan and the aldehyde group of glutaraldehyde produced acetalization and consumed part of the -OH.…”
Section: Ftir Analysismentioning
confidence: 97%
“…Similarly, in Figure 7b, it is seen that although the breakthrough times of the WKWS4 sample increase from 12.5 to 36.5, 66, and 93 min with the increase of adsorbent mass, the corresponding adsorption capacities of the adsorbent per unit mass are 15.179, 22.16, 20.035, and 18.821 mg/g, respectively. It is found that there is a maximum when the mass of the adsorbent is 0.1 g. Mohammadi et al 53 indicated that the increase of adsorbent mass could provide more adsorption sites and surface area. Therefore, adding more adsorbent can improve the adsorption capacity and promote the adsorption of H 2 S. However, due to the small cross-sectional area of the fixed reaction bed, adding too much adsorbent cannot produce better adsorption capacity of the adsorbent per unit mass.…”
Section: Study On Adsorptionmentioning
confidence: 99%